Occupational Therapists' Perceptions of Home Program Provision for Stroke Survivors in a Lower- and Middle-Income Country: An Exploratory Study. Issue 1 (3rd January 2023) - Malgaonkar, Neha; Ramachandran, Meena; Patel, Sefali Dushyant; Dsouza, Sebestina Anita
Abstract: This qualitative study aimed to understand occupational therapists' experiences of providing home programs to stroke survivors in India. Using an interpretative phenomenological approach, eight practicing occupational therapists were interviewed in depth about home programs for individuals recovering from stroke. Two broad themes with subthemes emerged describing the organizational factors, sociocultural and economic influences on home program provision as well as describing how the occupational therapists addressed the challenges to facilitate home program provision and adherence. The findings can inform occupational therapy practice in lower- and middle-income countries like India and other countries where existing practice recommendations for stroke rehabilitation and core professional tenets may be challenged.